P195. Impaired motor learning in older adults-concepts of underlying mechanisms and strategies for supporting impaired functions. Issue 8 (August 2015) - Timmermann, J.E.; Zimerman, M.; Wessel, M.J.; Gerloff, C.; Krakauer, J.W.; Hummel, F.C.
<x xml:space="preserve">Abstract</x> Introduction The aging population is facing important challenges associated to impairments in cognitive abilities including sensorimotor functions. In our daily life the acquisition and long-term retention of motor skills play a crucial role for the appropriate implementation of motor acts, such as practicing sport or the use of modern communication tools. Notably, motor cortical plasticity is altered in older adults (OA) due to changes in neurotransmission and synaptic functioning. Changes in GABAergic activity and its modulatory capacity has been described, as well as diminished LTP-like mechanisms contributing to associative plasticity and motor memory formation. Strong interest lies in the understanding of age-associated mechanisms underlying impairment of motor performance and motor learning in old and in possible ways of ameliorating age-related deficits in these domains. Methods Experiment 1: We investigated the process of learning of sequential finger tapping in a group of 15 healthy OA (73.9 ± 5.9 years ± standard deviation [SD]) and compared to 15 healthy young subjects (24.4 ± 3.5 SD). The learning process was accompanied by double-pulse transcranial magnetic stimulation (dp-TMS) in order to investigate intracortical effects during the learning process reflecting activity of GABAergic neurotransmission. The task was performed during 5 consecutive training days, with 3 follow-up time points on day 10, 20 and 60. Experiment 2: In a subsequent experiment, we investigated the effects of transcranial direct current stimulation (tDCS) in a group of 28 healthy OA aged 72.0 ± 5.4 SD. tDCS provides the possibility to modulate cortical excitability and neuroplasticity. We tested the hypothesis that tDCS in combination with training will enhance the effect of skill acquisition in OA. In our double-blind, placebo controlled study tDCS was applied to the motor cortex, contralateral to the training performing hand. Either anodal or placebo/sham stimulation was applied for 20 min while subjects underwent the same training as mentioned above. Results Experiment 1: Analyses revealed impaired skill acquisition in the OA group in relation to the young group during training period (pMOVE). The group of young healthy subjects showed learning related changes of SICIMOVE towards an enhanced event-related disinhibition. This was not the case for OA. Experiment 2: The group receiving real stimulation showed a different learning curve in the 5 days of training with significantly enhanced skill acquisition compared to the sham group (p = 0.044), a behavioral effect still apparent 60 days after interventions. Conclusions Motor skill acquisition was impaired in healthy older subjects, this effect was mainly driven by a reduction in offline effects. Furthermore, tDCS can ameliorate age-related deficits in the acquisition of a novel motor skill, offering a promising interventional strategy to address age-related cognitive deficits.